Stress and Interpersonal Relationships in Medical Students During Public Health Emergencies: A Network Analysis - Cui Y; Guo Z; Yang T; Zhang M; Mu H; Li J; Fang J; Du T; Yang X (Advances in Medical Education and Practice)
Yi Cui,1,* Zhihua Guo,2,* Tianqi Yang,2,3,* Man Zhang,4 Hezi Mu,5 Jiayao Li,1 Jiaxin Fang,6 Tianshu Du,1,2 Xiaomei Yang7 1Department of Nursing, Air Force Medical University, Xi’an, People’s Republic of China; 2Department of Military Medical Psychology, Air Force Medical University, Xi’an, People’s Republic of China; 3 93575 Unit of the Chinese People’s Liberation Army, Chengde, People’s Republic of China; 4Department of Nursing, Shaanxi Provincial People’s Hospital, Xi’an, People’s Republic of China; 5Department of Orthopedics, The Second Affiliated Hospital of Air Force Medical University, Xi’an, People’s Republic of China; 6Department of Nursing, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 7Department of Gynecology, Shaanxi Provincial People’s Hospital, Xi’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianshu Du, Department of Nursing, Air Force Medical University, Xi’an, 710000, People’s Republic of China, Email dutianshu1985@163.com Xiaomei Yang, Department of Gynecology, Shaanxi Provincial People’s Hospital, Xi’an, 710000, People’s Republic of China, Email XiaoMeiYang2081@outlook.comBackground: With the growing demand for medical services worldwide, especially during public health emergencies, medical students, as a special group of future medical workers, are important for the development of health services, and they therefore experience more stress than ordinary college students do. The mental health of medical students plays a vital role in their training, and interpersonal relationships are an important factor affecting their stress levels.Purpose: This study aims to investigate the network structure of stress and interpersonal relationships among Chinese medical students and identify bridge variables to prevent and relieve this stress.Patients and Methods: A self-report measurement taken from the Sociodemographic Questionnaire, Stress Scale for College Students and Interpersonal Relationship Synthetic Diagnosis Test was administered to 322 Chinese medical students from January to April 2022. Network analysis was used to determine the network structure, and the bridge expected influence (BEI) was identified as the bridge variable.Results: A total of 6.83% of the medical students experienced high levels of stress, and 31.06% of the medical students experienced various degrees of interpersonal distress. The edges across the community associated with stress and interpersonal relationships were all positive. The edges between S1 “personal hassle” and R3 “dealing with people”, S2 “academic hassle” and R2 “socializing”, and S3 “negative life event” and R4 “dating someone of the opposite sex” were the strongest. S1 “personal hassle” had the greatest BEI of the stress community (0.44), and R3 “dealing with people” had the greatest BEI of the interpersonal relationship community (0.19).Conclusion: This study used network analysis to investigate the relationship between stress and interpersonal relationships in Chinese medical students at the component level for the first time and highlight that the critical bridge variables “personal hassle” and “dealing with people” may contribute to preventing and relieving stress in Chinese medical students.Keywords: medical students, stress, interpersonal relationship, network analysis, public health emergency